The Administrative Code of the Republic of Moldova: Expectations and Reality: Array - Saitarli, Natalia (Journal of Danubian Studies and Research, 2020)
The article deals with the analysis of a new normative act in the Republic of Moldova Administrative Code: structure and content. The opinions of different authors regarding the systematization of the normative provisions. Conclusions referring to the systematization of the normative provisions in the Administrative Code of RM.